Navigating Consumer Happiness: The Impact of Product Quality, Service Standards, and Pricing in the E-commerce Landscape - Ernawati, Diah (Oikonomia: Jurnal Manajemen, 2025)
Purpose This study empirically proves the influence of product quality, excellent service and better and improved price perceptions will increase customer satisfaction. Methodology Selection of multivariate analysis design with quantitative cross sectional. Data collection from questionnaires announced to Perbanas students with convenience sampling techniques of 70 respondents who are active Tokopedia customers. Testing of this multivariate analysis model was selected with multiple regression assisted by the SPSS 26 application. Findings The results of the study indicate that the third independent variable has a positive and significant effect on consumer satisfaction. Product quality makes a major contribution to increasing customer satisfaction, excellent service quality provides a more comfortable shopping experience, and competitive prices are an important factor for satisfaction. Suggestions These findings provide insight for Tokopedia management in designing more effective strategies to increase customer satisfaction and loyalty, such as improving quality control of products sold. Thus, this study can be a reference for marketplace managers in developing more optimal marketing strategies to increase competitiveness in the e-commerce industry.